Hollow Ni/Co‐MOFs with Controllable Surface Structure as Electrode Materials for High Performance Supercapacitors. Issue 30 (12th September 2022) - Zhang, Xu; Liu, Zhiqing; Qu, Ning; Lu, Wang; Yang, Shixuan; Tian, Yuhan; Zhang, Qiang; Zhao, Yingyuan
Abstract: The metal‐organic frameworks (MOFs) with redox active metal ions and diverse organic linkers have been broadly investigated as the expecting electrode materials for supercapacitors. Here, the hollow Ni/Co‐MOFs with uniform and small protrusions can be obtained by a simple one‐pot solvothermal process, controlling the size of the protrusions on the MOFs surface by regulating the molar ratio between metal ions and trimesic acid linkers. The small protrusions can supply plenty of redox sites for the electrochemical reactions while the hollow spheres should offer sufficient contact area for the electrolyte to reduce the ion transport resistance. The prepared Ni/Co‐MOFs exhibit promising performance in the supercapacitors. The Ni/Co‐MOF with ratio of 1:1 (metal ions:trimesic acid linkers) gives outstanding performance that the specific capacity can reach 828 C g −1 when the current density is 1 A g −1 and the rate capability can reach 68% at 20 A g −1 . This work may cast light on tuning the structure of MOFs to boost electrochemical capacity. Abstract : The hollow Ni/Co‐MOFs with uniform and small protrusions have been fabricated by adjusting the ratio of the metal ions and trimesic acid. The uniform and small protrusions can supply plenty of redox sites for the electrochemical reactions while the hollow spheres should offer sufficient contact area for the electrolyte to reduce the ion transport resistance, exhibiting the excellent electrochemical performance.